PENGGUNAAN ANALISIS PEUBAH GANDA DALAM TAKSONOMI NUMERIK : CONTOH KASUS 2 KULTIVAR KEDELAI DAN KETURUNANNYA (F2) - Nina Ratna Djuita; Muhammad Jusuf (PTTI, 2006)
Nina Ratna Djuita & Muhammad Jusuf. 2006. The use of Multivariate Analysis in Numerical Taxonomy : Case of Two, Soybean Cultivars and Their Generation (F2). Floribunda 3(1): 10-18. — Multivariate analysis was applied to the morphological data of Slamet and Nokon Sawon cultivars and their generation (F2). This research was intended to compare multivariate analysis namely principal component analysis and disciminant analysis to two cultivars above and their generation. The first analysis resulted 2 and 7 principal components of covariance and correlation matrix for original data while data transformed revealed 5 and 8 principal components of covariance and correlation matrix respectively. Based on discriminant analysis, Nokon and Sawon’s cultivar can be successfully classified as a single group different from the rest.